2017
DOI: 10.1021/acs.jafc.7b02247
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-Oxide (PTIO) Radical Scavenging: A New and Simple Antioxidant Assay In Vitro

Abstract: Current in vitro antioxidant assays have several limitations, which frequently cause inconsistent results. The study develops a new antioxidant assay using the 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide radical (PTIO). After the investigation of various factors, the experimental protocol was briefly recommended as follows: PTIO and the sample solution were added to phosphate buffer (pH 7.4, 50 mM), incubated at 37 °C for 2 h, and then spectrophotometrically measured at 557 nm. The validation test b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 24 publications
2
109
0
Order By: Relevance
“…Several reports have suggested that ET is always accompanied by H + -transfer (proton transfer) in biological systems [45][46][47][48]. To evaluate proton transfer with butein and (S)-butin, we used a PTIO • scavenging assay established by our team [49]. In the assay, varying IC 50 values (the concentration with 50% radical inhibition or relative reducing power) were observed for the two isomers at different pH values (4.5, 6.0, and 7.4, shown in Table 1, and Supplementary Materials S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have suggested that ET is always accompanied by H + -transfer (proton transfer) in biological systems [45][46][47][48]. To evaluate proton transfer with butein and (S)-butin, we used a PTIO • scavenging assay established by our team [49]. In the assay, varying IC 50 values (the concentration with 50% radical inhibition or relative reducing power) were observed for the two isomers at different pH values (4.5, 6.0, and 7.4, shown in Table 1, and Supplementary Materials S1).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, (S)-butin had a pKa value of 7.11 at 3 -OH [50,51]. On the other hand, the PTIO • scavenging reaction in pH 4.5 aqueous solution is indicated as an ET process [49]. The effectiveness of the two isomers at pH 4.5 implies that they also had the potential for ET.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTIO • -scavenging colorimetric measurement was conducted in accordance with our method [44]. Briefly, the test sample solution (x = 0-10 µL, 1 mg/mL) was added to (20 − x) µL of methanol, followed by 80 µL of an aqueous PTIO • solution.…”
Section: Colorimetric Measurement Of Ptio • -Scavengingmentioning
confidence: 99%
“…The 1,1-diphenyl-2-picrylhydrazyl radical (DPPH•) assay and 2-Phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide (PTIO•) assay were performed according to a previous study (Li, 2017). In brief, 1 mg DPPH• or 1 mg PTIO• was dissolved into 24 ml ethyl alcohol and the ZHANG ET AL.…”
Section: Real-time Quantitative Pcr (Qpcr)mentioning
confidence: 99%